Loss of Nfat5 promotes lipid accumulation in vascular smooth muscle cells - Kappert, Lena; Ruzicka, Philipp; Kutikhin, Anton; Torre, Carolina de la; Fischer, Andreas; Hecker, Markus; Arnold, Caroline; Korff, Thomas (The FASEB journal, 2021)
The nuclear factor of activated T-cells 5 (NFAT5) is a transcriptional regulator of macrophage activation and T-cell development, which controls stabilizing responses of cells to hypertonic and biomechanical stress. In this study, we detected NFAT5 in the media layer of arteries adjacent to human arteriosclerotic plaques and analyzed its role in vascular smooth muscle cells (VSMCs) known to contribute to arteriosclerosis through the uptake of lipids and transformation into foam cells. Exposure of both human and mouse VSMCs to cholesterol stimulated the nuclear translocation of NFAT5 and increased the expression of the ATP-binding cassette transporter Abca1, required to regulate cholesterol efflux from cells. Loss of Nfat5 promoted cholesterol accumulation in these cells and inhibited the expression of genes involved in the management of oxidative stress or lipid handling, such as Sod1, Plin2, Fabp3, and Ppard. The functional relevance of these observations was subsequently investigated in mice fed a high-fat diet upon induction of a smooth muscle cell-specific genetic ablation of Nfat5 (Nfat5(SMC)−/−). Under these conditions, Nfat5(SMC)−/− but not Nfat5fl/fl mice developed small, focal lipid-rich lesions in the aorta after 14 and 25 weeks, which were formed by intracellular lipid droplets deposited in the sub-intimal VSMCs layer. While known for being activated by external stimuli, NFAT5 was found to mediate the expression of VSMC genes associated with the handling of lipids in response to a cholesterol-rich environment. Failure of this protective function may promote the formation of lipid-laden arterial VSMCs and pro-atherogenic vascular responses.
Gesehen am 03.11.2021